Selection of Virtual Meeting Platform Using AHP-Topsis Method (Case Study Indonesian Ministry of Defense Employees) - Nur Iskandar Zulkarnaen; Agung Triayudi; Endah Tri Esti Handayani (Jurnal Mantik, 2020)
This research combines the AHP (Analytical Hierarchy Process) and TOPSIS (Technique forOrder of Preference by Similarity to Ideal Solution) methods which are implemented in the Decision Support System (DSS) for selecting a virtual meeting platform in work from home activities during theCovid-19 pandemic of the Indonesian Ministry of Defense employees. This research was conducted basedon five criteria, namely price, maximum participant, ease of use, ease of setup, and user reviews. The spreadof the COVID-19 virus is currently increasing every day and has become a global pandemic. Based on acircular from the Secretary General of the Ministry of Defense to reduce the risk of spreading the COVID19 virus within the Indonesian Ministry of Defense, it is necessary to implement employee work from home(WFH) which is carried out alternately. For this reason, a suitable virtual meeting platform is needed tocarry out WFH activities to carry out work assignments online. So far, some employees are still trying tocompare the most ideal platform to be used for virtual meetings during WFH. With the existence of severaladvantages and disadvantages of each of these platforms, the author tries to research and help providesolutions by creating a decision support system for selecting the virtual meeting platform.